A critical survey into the factors contributingto the student dropout from technical colleges in Sri Lanka - Ranasinghe, R.A.S.T. (My University, 2012)
This study focuses a t t e n t i o n on the problem of student dropout with s p e c i a l reference to t e c h n i c a l education under the M i n i s t r y of Higher Education. Despite the r i s i n g demand f o r t e c h n i c a l and v o c a t i o n a l education and an increase i n job o p p o r t u n i t i e s f o r t r a i n e d p e r s o n n e l , i t has been observed that there i s a high rate of dropouts from t e c h n i c a l c o l l e g e s . The main o b j e c t i v e of t h i s study i s , t h e r e f o r e , to i d e n t i f y the courses of student dropout from t e c h n i c a l c o l l e g e s . It i s f u r t h e r expected t h a t t h i s study would create an awareness among the t e c h n i c a l education a u t h o r i t i e s , o f the acuteness of t h i s problem and what remedial measures could be taken to b r i n g down the r a t e of dropout. The p o p u l a t i o n f o r t he study c o n s i s t s of the 11 Grade I t e c h n i c a l c o l l e g e s and 12 Grade I I t e c h n i c a l c o l l e g e s under the M i n i s t r y of Higher Education, S r i Lanka. Purposive sampling was used i n the s e l e c t i o n of t e c h n i c a l c o l l e g e s from which the sample was drawn. Thus s i x t e c h n i c a l c o l l e g e s spread out i n d i f f e r e n t d i s t r i c t s were s e l e c t e d and the sample was drawn from these c o l l e g e s . However, the sample does not comprise r e p r e s e n t a t i on of t e c h n i c a l c o l l e g e s e s t a b l i s h e d i n Tamil speaking areas and a l s o other areas which are a f f e c t e d by the e t h n i c problem. Three q u e s t i o n n a i r e s were developed and administered to 3 samples drawn from the 6 t e c h n i c a l c o l l e g e s s e l e c t e d . The f i r s t sample c o n s i s t e d of 300 dropouts, the second c o n s i s t e d of 600 students f o l l o w i n g f u l l time day c l a s s e s while the t h i rd compriesed j}0 a d m i n i s t r a t o r s and teachers. Questionnaire I was mailed to 300 dropouts and q u e s t i o n n a i r e s I I ana I I I were : IX : administered to the respondents p e r s o n a l l y by the researcher. Percentages for the 14 causes f o r g i v i n g up t e c h n i c al caurses i n d i c a t e d i n q u e s t i o n n a i r e I were c a l c u l a t e d . The frequencies r e c o r d i n g the causes which might i n f l u e n c e the withdrawal d e c i s i o n s of students were worked out, i n accordance w i t h the degree of agreement. Graphical i l l u s t r a t i o n s were made and c o r r e l a t i o n metrix using Rank c o r r e l a t i o n c o e f f i c i e n t formula were prepared. One t a i l t values of s i g n i f i c a n c e were computed to determine the s i g n i f i c a n c e of i n t e r major f a c t o r s group a s s o c i a t i o n w i t h each other on the withdrawal d e c i s i o n s of students. Chi square values were computed on the d i s t r i b u t i o n a l percentage of each major f a c t o r i n q u e s t i o n n a i r e I I I . The respondent dropouts adduced more than one reason f o r t h e i r dropping out. Most important of a l l was f i n a n c i al d i f f i c u l t i e s and the f a c t o r s c l a s s i f i e d under socio economic group were given highest r a t i n g s . The respondents f o r the second q u e s t i o n n a i r e r a t e d the highest degree of agreement i n respect of the statement, " 'Parents/guardians want the student to f i n d a job to support the f a m i l y ' 11. It i s evident that even i n the case of these respondents, socio economic f a c t o r s w i l l have a s i g n i f i c a n t i n f l u e n c e on t h e i r p e r s i s t e n c e / w i t h d r a w a l d e c i s i o n s. I t i s , recommended that a stipend be provided to t e c h n i c al c o l l e g e students and also r e s i d e n t i a l f a c i l i t i e s at l e a s t i n areas where board and lodging fees are high. The duration of t e c h n i c al courses should be reviewed and the c u r r i c u l a r e v i s e d . The system of e v a l u a t i o n , c e r t i f i c a t i o n and a c c r e d i t a t i o n need be i n v e s t i g a t e d